2014
DOI: 10.1186/s40543-014-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalytical method for quantification of Solifenacin in rat plasma by LC-MS/MS and its application to pharmacokinetic study

Abstract: Background: Solifenacin succinate is a competitive muscarinic acetylcholine receptor antagonist used in the treatment of overactive bladder with or without urge incontinence. Methods: Liquid chromatography-tandem mass spectrometry method was used for quantification of Solifenacin (SF) in rat plasma. Solifenacin-d5 (SFD5) used as an internal standard. Chromatographic separation was performed Gemini-NX C18, 50 × 4. Conclusions: This method is successfully applied in the Pharmacokinetic study of rat plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The peak area ratio against maralixibat concentration was used to construct a calibration graph [17][18][19]. The findings were discovered to be linear across the 5.00-100.00 ng/ml concentration levels.…”
Section: Linearitymentioning
confidence: 99%
“…The peak area ratio against maralixibat concentration was used to construct a calibration graph [17][18][19]. The findings were discovered to be linear across the 5.00-100.00 ng/ml concentration levels.…”
Section: Linearitymentioning
confidence: 99%
“…Therapeutic indication of this brand is to treat moderate to severe storage symptoms like urgency, increased micturition frequency and voiding symptoms associated with benign prostatic hyperplasia (BPH) in men who are not adequately responding to treatment with monotherapy [3] . Literature survey reveals spectrophotometric methods [4][5][6][7][8] , High Performance Liquid Chromatography (HPLC) [9][10][11] and Liquid Chromatography-Electrospray Ionization-Mass Spectrometry (LC-ESI-MS/MS) [11][12] methods were available for tamsulosin hydrochloride and Ultraviolet [13][14] , HPLC [15][16] , Ultra-Performance Liquid Chromatography (UPLC) [17] , high-performance thin layer chromatography (HPTLC) [18] and Liquid Chromatography with tandem mass spectrometry (LC-MS/MS) [19][20] methods were available for estimation of solifinacin succinate. Only few reverse phase high performance liquid chromatography (RP-HPLC) [21][22] method and spectrofluorimetric [23] methods were reported for the estimation of solifinacin succinate & tamsulosin hydrochloride in combination dosage forms.…”
Section: Chemically Tamsulosin Hydrochloride Is 5-[(2r)-2-{[2-(2-ethoxyphenoxy)ethyl]mentioning
confidence: 99%
“…Literature survey revealed that few chromatographic methods for SOLS [6][7][8][9][10][11][12][13][14][15][16][17], FLXHC [18][19][20][21] and TOLT [22][23][24][25][26][27][28][29], spectrophotometric methods for SOLS [30,31], FLXHC [32,33] and TOLT [34][35][36], potentiometric method Equivalent weights of 10 mg of SOLS, 20 mg of FLXHC and 20 mg of TOLT were transferred into three 100 mL clean dry volumetric flasks containing 70 mL of mobile phase and the mixture was sonicated to dissolve the powder. The volume was made up to the mark with the same solvent.…”
Section: Preparation Of Pharmaceutical Dosage Forms Solutionsmentioning
confidence: 99%